Prospects and Challenges Faced by Secondary Teachers while Integrating ICT in Nepalese ESL Classrooms - Khadka, Kabita (Dristikon: A Multidisciplinary Journal, 2021)
Teaching and learning in the 21st century has been embedded with technology. Use of Information and Communication Technology (ICT) plays a crucial role in ameliorating knowledge acquisition in general and enhancing English Language mastering in particular. The government of Nepal has made provision of integrating ICTs in school education to enhance quality education and make both teachers and learners confident and competitive in the present global world. The teachers are the real implementers of the policy into practice. In this context, this research intends to investigate secondary level English teachers’ skill and motivation in using ICTs while teaching the English language. This is a qualitative study that uses a phenomenological approach to obtain information according to Denzin (2019) in which the participants in the study included eight schools and 16 teachers at different schools in Nepal. They were selected purposefully since selecting the best participant ensures the intended information (Creswell & Creswell, 2017). The telephonic interview was conducted and open-ended questions were administered electronically and all necessary directions were provided to them so that they could respond to those questions. The findings imply that teachers should be given opportunities for training on ICT use for building up their skill, motivation, knowledge and confidence.